Application of reactive siloxane prepolymers for the synthesis of thermoplastic poly(ester-siloxane)s and poly(ester-ether-siloxane)s - Antić Vesna V.; Vučković Marija V.; Đonlagić Jasna (Journal of the Serbian Chemical Society, 2007)
Thermoplastic poly(ester-siloxane)s (TPES) and poly(ester-ether-siloxane) s, (TPEES), based on poly(butylene terephthalate) (PBT) as the hard segment and different siloxane-prepolymers as the soft segments, were prepared. The TPES and TPEES were synthesized by catalyzed two-step transesterification from dimethyl terephthalate, (DMT), 1,4-butanediol, (BD) and a siloxane-prepolymer. Incorporation of dicarboxypropyl- or disilanol-terminated poly(dimethylsiloxane)s (PDMS) into the polar poly(butylene terephthalate) chains resulted in rather inhomogeneous TPES copolymers, which was a consequence of a prononuced phase separation of the polar and non-polar reactants during synthesis. Two concepts were employed to avoid or reduce phase separation: 1) the use of siloxane-containing triblock prepolymers with hydrophilic terminal blocks, such as ethylene oxide (EO), poly(propylene oxide) (PPO) or poly(caprolactone) (PLC) when the terminal blocks serve as a compatibilizer between the extremely non-polar PDMS and the polar DMT and BD, and 2) the use of a high-boiling solvent (1,2,4-trichlorobenzene) during the first phase of the reaction. Homogeneity was significantly improved in the case of copolymers based on PCL-PDMS-PCL. .